«Faccio delle cose coi libri» Calvino vs anni Settanta - Paolo Giovannetti (Enthymema, 2012)
If on a Winter Night a Traveller negatively judges the 1970s and, in particular, Italian 1970s, in that it denounces the political and ideological excesses of this decade. Interestingly, this stance is reflected in the text on the formal level. In fact, the second-person narrative of the novel aims, on the one hand, to manipulate the reality of the 1970s as a whole, to the extent that it is totally erased. On the other, this stylistic choice defends the role of the author and its ability to control the act of reading.